Extended Working Lives in Denmark and Finland: Influences of Computerization - Komp-Leukkunen, Kathrin (Nordic Journal of Working Life Studies, 2024)
Extended working lives become important in aging populations. Yet, for a long time, increasing computer use pushed older individuals out of the workforce. Recently, older workers’ computer skills have improved. This article investigates how computer use, experience, and training affect workforce participation in old age in countries with widespread computer use. It conducts regression analyses of Danish and Finnish survey data. Findings show that individuals who used computers had a higher chance of remaining in the workforce. Computer experience made older Finns marginally more likely to retire. However, computer training had no influence. Findings suggest that the relevance of computer use for extended working lives depends on a country’s computerization level: the higher the level, the less of an obstacle to extended working lives computerization presents. Policymakers should facilitate older workers’ computer use especially when computers are first introduced, and explore alternative means for extending working lives afterwards.